2023
DOI: 10.3389/fcell.2023.1182204
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid receptor regulation of decision-making for cell differentiation

Abstract: All-trans retinoic acid (ATRA) activation of retinoic acid receptors (RARs) is crucial to an organism’s proper development as established by findings for mouse foetuses from dams fed a vitamin A-deficient diet. ATRA influences decision-making by embryonic stem (ES) cells for differentiation including lineage fate. From studies of knockout mice, RARα and RARγ regulate haematopoiesis whereby active RARα modulates the frequency of decision-making for myeloid differentiation, but is not essential for myelopoiesis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 90 publications
1
6
0
Order By: Relevance
“…RA can regulate stem cell phenotype maintenance versus differentiation in ESCs as well as in CSCs [23,26]. In the present study, we found that RA acutely hinders the viability of SK-ES-1 ES cells; increases expression of CDKN1A, p21, and CD99 while reducing expression of SOX2 and TUBB3; and impairs the formation of ES tumorspheres with high expression of SOX2 and Nestin.…”
Section: Discussionsupporting
confidence: 55%
“…RA can regulate stem cell phenotype maintenance versus differentiation in ESCs as well as in CSCs [23,26]. In the present study, we found that RA acutely hinders the viability of SK-ES-1 ES cells; increases expression of CDKN1A, p21, and CD99 while reducing expression of SOX2 and TUBB3; and impairs the formation of ES tumorspheres with high expression of SOX2 and Nestin.…”
Section: Discussionsupporting
confidence: 55%
“…ATRA is recognized for its pivotal involvement in fundamental cellular processes such as growth (including in bones), differentiation, and organogenesis [125,126]. Through its specific binding to the RARs located in target cells, ATRA operates as a transcriptional regulator, modulating the expression of genes crucial for cell differentiation, proliferation, morphogenesis, and tissue development [127][128][129]. This regulatory mechanism orchestrates the intricate process of cell specialization and the formation of distinct tissues and organs during embryonic development [130].…”
Section: Growth Cellular Differentiation Morphogenesis and Reproducti...mentioning
confidence: 99%
“…Vitamin A is an essential nutrient as animals cannot synthesize it [40]. ATRA drives differentiation in many different cell lineages and settings [41]. It is also used as a pharmaceutical driver of differentiation in pediatric neuroblastoma and pediatric acute promyelocytic leukemia [42][43][44].…”
Section: Atramentioning
confidence: 99%